Percutaneous Puncture Embolization for Recurrent Pulmonary Arteriovenous Malformation After Failed Initial Treatment: A Case Report. (February 2023) - Chen, Lumin; Liu, Yuyu; Chen, Renbiao
Background: Transcatheter embolization is a commonly used minimally invasive technique in the treatment of pulmonary arteriovenous malformation (PAVM) with a high probability of post-operative recurrence, and some recurrent cases of PAVM cannot be treated via pulmonary arterial re-embolization. Here, we report the first case, to our knowledge, a 55-year-old female undergoing percutaneous direct puncture embolization for recurrent PAVM with good short-term efficacy. Case Presentation: The patient was a 55-year-old female presenting to the emergency department of our hospital with acute exacerbation of chest tightness and shortness of breath for 2 hours. The patient was diagnosed with PAVM and undergone embolization half a year ago. DSA-guided embolization was performed through percutaneous puncture approach. After embolization with four spring coils, the blood flow to the PAVMs was stopped and the surgery completed. The patient reported improvement of chest tightness and shortness of breath and was discharged from the hospital 3 days later. Conclusion: Our case was unique as a portion of the PAVMs was closely attached to the chest wall and PVP was slightly increased, which made percutaneous puncture embolization possible. Our case can be helpful in the treatment of recurrent PAVM in patients who cannot undergo re-embolization through pulmonary artery.